Is there a carry trade channel of monetary policy in emerging countries? - Kornél Kisgergely (Magyar Nemzeti Bank, 2012)
This paper empirically tests whether monetary policy can have a perverse effect on aggregate demand in emerging economies, because of short-term speculative inflows. For this purpose, a bayesian VAR is estimated on a panel of six major emerging countries. Monetary and risk shocks are identified by imposing only very mild restrictions. It is found that a positive interest rate shock results in a persistent decline in production and inflation. The net foreign asset position even improves in most of the countries. Thus no large net inflows are observed and there is no sign of a perverse effect on aggregate demand. More interestingly, central banks loosen interest rate policy significantly and persistently in the face of a capital inflow shock, possibly to dampen the immediate disinflationary effect of the appreciation and/or to protect balance sheets from exchange rate volatility. In some specifications this results in overheating (positive industrial production gap and inflation) in the medium-term. Thus central banks might amplify the effect of risk premium shocks by cutting interest rates - rather than raising them - when capital flows in.
Keywords: C11; C33; C54; E44; E58; F32; 330; carry trade; monetary policy; emerging markets